Evaluasi dan Peningkatan Kualitas Interaksi Pengguna pada Sistem Informasi Akademik MASTER menggunakan User-Centered Design dan SUPR-Q - Satria Tegar Bimantara; Muhammad Syaibani Al Hakim; Hermawan Setiawan; David Sam Limbong; Rahadian Ronggo Kusumo; Damar Damar (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
The "MASTER" academic information system currently exhibits critical limitations in user experience. Heuristic evaluation identified major issues in consistency, standards, and recognition rather than recall (severity 4), causing high cognitive load and disorientation due to a flat-list navigation structure. This research aims to redesign the interface using the User-Centered Design (UCD) approach based on ISO 9241-210. Design solutions were developed to address user needs for structured navigation, task-hierarchy menu grouping, and quick access to the Semester Learning Plan (RPS) module. These solutions applied principles of visual hierarchy and the separation of academic and administrative functions. A subsequent evaluation using the SUPR-Q instrument with 30 respondents showed significant improvements in Loyalty (+1.20), Appearance (+0.72), and Trust (+0.70), achieving a 96.67% user preference rate for the new design. Although there was a slight decrease in usability (-0.06) indicating a temporary user adaptation period, findings demonstrate that the UCD application effectively reduces cognitive load, increases navigation efficiency, and enhances the overall user experience quality.